TİP 1 DİYABETİKLERİN ERKEN VE GEÇ DÖNEMİNDE ANTİOKSİDAN STATÜ - GÜZEL, Savaş; SEVEN, Arzu; CİVELEK, Sabiha; SALMAN, Serpil; SATMAN, İlhan; BURÇAK, Gülden (Cerrahpaşa Medical Journal, 2019)
Background and Design.. In this study, endogenous erythrocyte antioxidant status markers . CuZn superoxide dismutase (CuZn SOD), glutathione peroxidase (GSH Px), glutathione (GSH) . and plasma levels of vitamin C and E were investigated in 15 type 1 diabetics at onset (0-2 months) and at 18 months of diabetic age and in 15 healthy controls. Results.. In type 1 diabetics at onset significantly higher GSH (p<0.001), CuZn SOD (p<0.05), vitamin C (p<0.001) levels and significantly lower GSH Px (p<0.001) activity and at 18 months of diabetic age significantly by higher GSH Px (p<0.05) and significantly lower CuZn SOD (p<0.001) levels were observed in comparison to controls. At 18 months of diabetic age significantly decreased GSH (p<0.001), CuZn SOD (p<0.001) and vitamin C (p<0.01) levels and significantly increased GSH Px (p<0.01) and vitamin E (p<0.05) levels were observed compared to diabetics at onset. NO correlation was obtained between GHb and antioxidant status parameters. Conclusion.. Our findings reveal selective modification of antioxidant defense system as an adaptive response to oxidative stres in type 1 diabetics at onset and at 18 months of diabetic age.